Crescimento pró-pobre na América Latina: análise do período 2000-2014 para 18 nações - Artigas Nunez, Oswaldo Daniel (2019)
This study analyzes the quality of economic growth presented in Latin America in relation to its capacity to reduce poverty, during the period 2000-2014 to 18 Latin American nations. Using econometric models in dynamic panel data, income-poverty and inequality-poverty elasticities were estimated in the period before and after the global financial crisis. Likewise, using the LSDV model, the individual elasticities for each country were estimated. The results suggest that the Latin American growth process in the analyzed period benefited relatively the poorest part of the population. The dependence of the elasticities of the values of the average income and the concentration of income is highlighted. In this sense, the higher the mean income, the greater the absolute value of elasticity and the higher the concentration the lower the absolute value of elasticity. The results also suggest differences in the growth for the countries, with the countries of northern Central America having the lowest pro-poor growth rates and countries such as Brazil and Argentina, the largest. Also, the study concludes that economic growth is a necessary but not sufficient condition to reduce poverty in the region, and it is necessary to be accompanied by falls in inequality indices, which are high in the region. Finally, the results of the inequality-poverty elasticities suggest that Latin America went through a period in which poverty declined, but the rich became richer, which could, according to specialized economic theory, be a factor that made it lighter reduction of poverty.